Nutrimentum vascularum as pulsatile tinnitus - Narayankar, Nivedita M.; V., Chandre Gowda B.; Rai, S. Juthika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Tinnitus is one of the most common otological symptoms encountered in otorhinolaryngology. In recent times our understanding of tinnitus has significantly progressed but nonetheless, it still constitutes a very incapacitating symptom which greatly affects the quality of life. Objective tinnitus accounts for only 5% and has various aetiologies both non-otological and otological which include both non vascular and vascular. Vascular malformations like dural arteriovenous fistulas (DAVFs) constitute about 10% of objective tinnitus and hence are of academic interest to an otolaryngologist due to their rarity. We present one such case. A 26-year-old female presented to the department of ENT with chief complaints of a left pulsatile tinnitus of 2 months duration. A detailed clinical examination revealed no abnormality. A pure tone audiometry (PTA) was then done which once again showed hearing within normal limits. Given the clinical persistence of the symptom which was affecting her daily activities, further investigation of magnetic resonance imaging (MRI) brain was done. A suspicion of a dural arterio-venous fistula in the transverse sinus further warranted an arteriography which showed a low grade DAVF at the level of the left sigmoid sinus. DAVFs, although infrequent, constitute a treatable cause of tinnitus and hence should be considered as a possible diagnosis in all patients with pulsatile tinnitus, especially if it is unilateral. We also carried out a review of the current medical and surgical management in an attempt to better understand this rare yet intriguing condition.